Doktrin Objektivisme Ilmu Pengetahuan Modern - Syamsuri Syamsuri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2013)
This paper proves that the doctrine of scientific objectivism which then leads as the final truth in the world of science is only a figment, due to the fact that the main method used in the world of science it self contains a lot of weaknesses. Therefore, scientific truth is not the only truth that is needed and used as guidance for human life, but there are other truths which are so necessary to complement the scientific truth.DOI: 10.15408/ref.v13i4.909